The math behind the music - Harkleroad, Leon, 1955-; Cambridge University Press (Cambridge ; New York : Cambridge University Press, 2006)
Accompanying Audio CD contains music examples from the text
Preface -- Acknowledgments -- 1. Mathematics and music, a duet -- 2. Pitch : the ground of music -- 3. Tuning up -- 4. How to vary a theme mathematically -- 5. Bells and groups -- 6. Music by chance -- 7. Pattern, pattern, pattern -- 8. Sight meets sound -- 9. How not to mix mathematics and music -- Bibliography -- Contents of the CD -- Illustration credits -- Index
Includes bibliographical references (pages 129-134) and index
Accompanying Audio CD system requirements: IBM PC or compatible; Windows; media player; audio capability and speakers; CD-ROM drive
Keywords: Music in mathematics education; Mathematics -- Study and teaching; Music theory -- Mathematics; Music -- Acoustics and physics; Pattern formation (Physical sciences); Composition (Music)